Health education for children - Gupta, D. K. (Delhi : Khel sahitay kendra, 2003)
Compiled to offer a guideline on various aspects of health relating especially to children. This book is presented in an easy to follow format that will be useful to all children and parents alike.
Keywords: Children -- Health and hygiene; Health education